Haloplumbate salts as reagents for the non-aqueous electrodeposition of lead. Issue 77 (2nd August 2016) - Bartlett, Philip N.; Burt, Jennifer; Hasan, Mahboba M.; Hector, Andrew L.; Levason, William; Reid, Gillian; Richardson, Peter W.
Abstract : Cyclic voltammetry experiments on the Pb(ii ) salts, [PPh4 ][PbX3 ] (X = Cl, Br, I) in CH2 Cl2 solution ([PPh4 ]X supporting electrolyte) at Pt electrodes show reproducible nucleation and stripping features consistent with reduction to elemental Pb. Abstract : Cyclic voltammetry experiments on the Pb(ii ) salts, [PPh4 ][PbX3 ] (X = Cl, Br, I) in CH2 Cl2 solution ([PPh4 ]X supporting electrolyte) at a Pt disk electrode show reproducible nucleation and stripping features consistent with reduction to elemental Pb. The reduction potential shifts to less cathodic from Cl (−0.40 V) → Br (−0.27 V) → I (−0.19 V vs. Ag/AgCl), in line with the Pb–X bond strengths decreasing. Potentiostatic electrodeposition using [PPh4 ][PbCl3 ] in CH2 Cl2 leads to growth of a thin film of crystalline Pb onto planar TiN electrodes, confirmed by SEM, EDX and XRD analysis. Electrodeposition under similar conditions onto a planar Au electrode leads to deposition of elemental Pb, accompanied by some alloying at the substrate/film interface, with XRD analysis confirming the formation of AuPb2 and AuPb3 . Transferring the [PPh4 ][PbCl3 ] reagent into supercritical CH2 F2 (17.5 MPa and 360 K) containing [PPh4 ]Cl led to very limited solubility of the Pb reagent; using [N n Bu4 ]Cl as a supporting electrolyte caused an increase in solubility, although still lower than in liquid CH2 Cl2 . Cyclic voltammetry experiments (Pt disk) using this electrolyte also show voltammetry consistent with Pb deposition, however the low solubility of the lead salt in scCH2 F2 meant that electrodeposition onto a planar TiN substrate was not possible.